Challenges in the Diagnosis and Management of Celiac Disease - Nichols, Emma Hitt (MD Conference Express, 2015)
Awareness of celiac disease is rising, yet its diagnosis remains challenging, and many patients remain undiagnosed. In addition, many patients continue to experience symptoms despite adopting a gluten-free diet. Noncompliance, cross-contamination, and other conditions can cause symptoms to persist. Refractory disease is associated with lymphoma, which is associated with poor survival.